Deposition of hybrid sol-gel films on hot dip galvanized reinforc-ing steel - Figueira, R. B. (2013)
A functionalized siloxane and five amino terminated oligopolymers were used to produce, by sol-gel method and using a dip-coating process, OIH coating films as an alternative pre-treatment to prevent the corrosion of galvanized steel in concrete. The influence of residence time (RT), cure and number of dip steps on the coverage and uniformity of the obtained coatings dipped at a withdrawal speed of 10 mm min-1 for each oligopolymer were studied. The surface morphology and the depth chemical composition of the obtained coatings were analysed by SEM/EDS and GD-OES techniques. The results showed that the coverage and uniformity of the hybrid coating deposited on the HDGS surface improves with the increase on RT and number of dip steps. Nevertheless, full coverage is seldom achieved and the final OIH coatings thickness is very irregular.